PELATIHAN PENGEMBANGAN AGRO EDU WISATA MENUJU SMART VILLAGE YANG BERKELANJUTAN PADA KELOMPOK MILENIAL - Garnia, Erna; Nurwathi, Nurwathi; Perdana, Rangga Satria; Hadijah, Hady Siti; Maharani, Lisya; Fahrulrozi, Muhamad; Lisaumi, Siti Riyyan (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Agro edu-tourism is an alternative to community economic development, especially in rural areas, which can increase the income and welfare of local residents through the tourism and agriculture sectors. Sindulang Village is one of the villages that has great potential in the agricultural and tourism sectors. With this great potential, the Sangga Buana University Community Service team together with partners from local millennial groups aim to make the agricultural land area in Sindulang Village an Agro Edu Tourism object towards a sustainable Smart Village. One of the important factors to achieve the realization of the objectives of this activity is by improving the quality of human resources of partners. Several problems were found that became obstacles to the realization of agro edu tourism development in terms of knowledge about the agricultural production process, digital marketing-based marketing, and Tourism Awareness Groups. The method of implementation in this activity is by conducting training, demonstrations, and discussions with service partner participants. The results of the implementation of the training increased understanding and knowledge of the material raised from the obstacles experienced. So that after the training is carried out, agro edu tourism planning towards a smart village which is the goal of this activity can be continued by looking at various other factors, guidance on utilizing digital marketing, keeping financial records, photography, managing the development of tourism packages, and handling tourism risk management.